Implicit Mean Value and Certainty Equivalence - Fishburn, Peter C. (Econometrica, 1986)
This paper considers a generalized mean value m(p) defined implicitly for a probability measure p on the reals as the unique y for which J +(x, y) dp(x) = 0, where 0 is skewsymmetric and strictly increasing in its first argument. Conditions on m that are necessary and sufficient for the implicit characterization are given and its relationship to certainty equivalence is discussed.